2010
DOI: 10.1016/j.jtbi.2010.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stoichiometric, thermodynamic and kinetic modelling of steady state metabolism

Abstract: The quantitative analysis of biochemical reactions and metabolites is at frontier of biological sciences. The recent availability of high-throughput technology data sets in biology has paved the way for new modelling approaches at various levels of complexity including the metabolome of a cell or an organism. Understanding the metabolism of a single cell and multi-cell organism will provide the knowledge for the rational design of growth conditions to produce commercially valuable reagents in biotechnology. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 48 publications
(65 reference statements)
1
44
0
Order By: Relevance
“…In addition, unrealistic fluxes can be predicted in silico if a reaction is reversible in a model, but irreversible in vivo . Thus, methods are now applying more rigorous thermodynamic constraints (Figure 2) by removing thermodynamically infeasible pathway usage 9597 or constraining flux based on Gibbs free energy calculations 51, 98, 99 . Methods are also being used to infer thermodynamic parameters 100 .…”
Section: A Phylogeny Of Constraint-based Methodsmentioning
confidence: 99%
“…In addition, unrealistic fluxes can be predicted in silico if a reaction is reversible in a model, but irreversible in vivo . Thus, methods are now applying more rigorous thermodynamic constraints (Figure 2) by removing thermodynamically infeasible pathway usage 9597 or constraining flux based on Gibbs free energy calculations 51, 98, 99 . Methods are also being used to infer thermodynamic parameters 100 .…”
Section: A Phylogeny Of Constraint-based Methodsmentioning
confidence: 99%
“…Another potential area for improvement of gap-filling methods is the inclusion of thermodynamic information. Several studies have already shown that the inclusion of thermodynamic constraints can improve the accuracy of constraint-based model predictions (Beard et al 2004; Fleming et al 2009; Fleming et al 2010; Henry et al 2006). So far, only studies using BNICE and the modified GrowMatch used to improve the iBsu1103 B. subtilis model have considered thermodynamic constraints when making gap-filling predictions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of promising approaches has been proposed for incorporating metabolite-level information into genome-scale metabolic models. [51][52][53][54] The goal of these modeling approaches is to use incomplete metabolite-level or metabolic-flux measurements to determine the metabolic state (both fluxes and concentrations) of the cell as completely and accurately as possible. The combination of statistical and mechanistic modeling strategies presents a promising strategy to leverage the strengths of both approaches for future design of improved cell factories.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%